2005
DOI: 10.1345/aph.1g194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing, Long-Term Storage, and Microwave Thawing on the Stability of Ketorolac Tromethamine

Abstract: Within these limits, ketorolac tromethamine in dextrose 5% infusion may be prepared and frozen in advance by a centralized intravenous admixture service, then thawed before use in clinical units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Ampicilline need temperature of storage from -30 • C to -70 • C, not currently obtained with a majority of freezers [27]. Azlocillin [28], carbenicillin [26,28,29], piperacillin [62,63], temocillin [65], ticarcillin [27,48], support MFTT. Stability for storage after thawing was evaluated for ampicilline [27], carbenicilline [26] and ticarcilline [27,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ampicilline need temperature of storage from -30 • C to -70 • C, not currently obtained with a majority of freezers [27]. Azlocillin [28], carbenicillin [26,28,29], piperacillin [62,63], temocillin [65], ticarcillin [27,48], support MFTT. Stability for storage after thawing was evaluated for ampicilline [27], carbenicilline [26] and ticarcilline [27,48].…”
Section: Discussionmentioning
confidence: 99%
“…The stability for storage after thawing was evaluated [26,27,43,48]. Combinations of penicillins and beta-lactamases (J01CR: piperacilline + tazobactam) was submitted with success to MFTT and can be stored after thawing [62]. In the first generation of cephaslosporins (J01DB): cefazolin [22,28], cephalotin [26], cephapirin [41] remains chemically stable during MFTT and can be stored after thawing [22,26,28,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moon and others 2 reported that solutions of tazobactam (10 mg/mL) and piperacillin (80 mg/mL) in both D5W and NS were stable for 30 days when stored at -15°C. Hecq and others 3 found that solutions of tazobactam (4.4 mg/mL) and piperacillin (33.3 mg/mL) in D5W retained above 90% of the initial concentration for 35 days when stored at 4°C after freezing and microwave thawing. Rigge and Jones 4 reported that the combination of tazobactam (5 mg/mL) and piperacillin (40 mg/mL) in NS stored in PVC bags was stable for 5 days at 7°C and 4 days at 25°C, irrespective of exposure to light.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, folinate salt (racemic) and its long-term stability in dextrose 5% infusion at 5 ± 3°C has been successfully studied in our institution (5), showing a concentration above 90% of the initial concentration during 30 days at least. Freeze-thaw treatment extends long-term storage of infusions (6), and the use of microwave oven reduces thawing time required for frozen infusions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Combining these two methods, make time management easier for centralized hospital pharmacy service to prepare drugs and to improve safety by reducing workload and its potential consequence in preparation errors (17).…”
Section: Introductionmentioning
confidence: 99%